KRITIK SOSIAL DALAM KUMPULAN PUISI BERTEMA TEKNOLOGI - Iwan Sulistiawan (Sekolah Tinggi Pariwisata Mataram, 2022)
The research aims to see how ideas of ten Indonesian prominent poets in their poems that were categorized as poems with current technology topic by www.sepenuhnya.com, function as social criticism of the negative impacts of technology. The method used is descriptive qualitative in a sociology of literature approach that regards literary work as social document or the expression of its society. The result of the research shows that all the poems did their function as conveying social criticism towards technology. The social criticism comprises all aspects of the negative impacts of technology, namely physical, psychological, social and environmental. These poems of technological topic are also categorized as obvious and prosaic poems of which ideas are easy to comprehend and do not open the potential of multi-interpretation